3rd IEEE International Symposium on Biomedical Imaging: Macro to Nano, 2006.
DOI: 10.1109/isbi.2006.1625150
|View full text |Cite
|
Sign up to set email alerts
|

Atlas-Assisted Tomography: Registration of a Deformable Atlas to Compensate for Limited-Angle Cone-Beam Trajectory

Abstract: We present a method to improve the quality of cone-beam tomographic images computed from an intra-operative C-arm scan by adding information from an anatomical atlas. Limited range of C-arm view angles leads to reconstruction artifacts and poor anatomical detail. We propose to complete the missing views with simulated projections of a statistical anatomical model, which is deformably registered to match the data in the C-arm images. This paper presents the methods used to create the atlas and to register it wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(8 reference statements)
1
13
0
Order By: Relevance
“…In a previous publication [1], we showed that a deformably registered anatomical model can be combined with a limited-trajectory set of x-ray images to create a CT-like "hybrid reconstruction". The current paper focuses on assessing the accuracy of our deformable registration.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous publication [1], we showed that a deformably registered anatomical model can be combined with a limited-trajectory set of x-ray images to create a CT-like "hybrid reconstruction". The current paper focuses on assessing the accuracy of our deformable registration.…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of our approach include: 1) very minimal initial segmentation is required (once to create an initial mesh) and may be done manually or semi-automatically; 2) point correspondences are established automatically through intensity-based registration, avoiding landmark selection; 3) atlas bias/uncertainty is minimized through iterative refinement of an initial atlas; 4) the method requires little or no explicit prior anatomical information, although such information may be added in a separate annotation phase; and 5) the atlases produced are useful as prior information for assisting 3D/3D and 2D/3D (e.g., [5]) registration, as well as assisting in tomographic reconstruction from incomplete data [5].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical characterization using principal component analysis (PCA) and point distribution models is presented in [1]. Following Cootes et al, a number of authors (e.g., [2], [3], [4], [5]) have applied similar methods to construct statistical atlases of bony anatomy from CT scans of multiple individuals. The basic method used is to identify landmark points, establish point-based correspondences between subjects, and then perform statistical analysis to study shape variations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations